An Analysis Content Validity of English Summative Test Items of The Eleventh Grade at SMAN 1 Batangan in Academic Year 2023/2024 - Ida Khudriyah; Diah Kurniati; Muh Syafei (Universitas Muria Kudus, 2025)
It is necessary to analyze the learners' performance in a foreign language. Furthermore, a lot of teachers still struggle with the exam item analysis. It is employed to determine the learners' accomplishments. If not, the teachers continue to struggle to assign grades. It is intended that they are unable to determine whether the students are making progress. The report also attempts to provide an analysis of the test item's content validity. Finding out if a test is acceptable for the curriculum requires analyzing its content validity.Â Â The goals of this study are to measure the validity of test items for the eleventh grade at SMA Negeri 1 Batangan and to offer information about the quality of English summative exam items. The English summative test items from the first semester of the eleventh grade students at SMAN 1 Batangan were examined for conformity and nonconformity with the learning indicators. The students' answer sheets and the summative exam were the sources of the data. There are forty multiple-choice questions on the test, representing the answers of forty students. According to the research's findings, 31 items, or 77,5%, meet the standards to conform to the learning indicators, whereas 9 items, or 32,5%, do not. This indicates that the English summative test items for the eleventh grade students at SMAN 1 Batangan have a good content validity.